Material Extrusion Additive Manufacturing of Metal Powder‐Based Inks Enabled by Carrageenan Rheology Modifier. Issue 2 (15th October 2020) - Pack, Robert Cody; Compton, Brett Gibson
Abstract : A new carrageen‐based route to produce metal powder‐based inks tailored for direct ink write additive manufacturing is presented. Aqueous‐based inks are formulated with carrageenan, a red seaweed‐derived polysaccharide, that serves as both a binder and viscosifier, along with 316L stainless steel or nickel powders and dispersants. Thermogravimetric analysis, scanning electron microscopy, and rheological measurements are performed to characterize carrageenan burnout, metal particle morphology, and formulated ink behavior, respectively. Simple (rectangular) and complex (honeycomb and lattice) metallic architectures are 3D‐printed via material extrusion, dried, and pressurelessly sintered in an inert argon atmosphere to produce densified structures. 316L structures exhibit up to 94% theoretical density, attributed to a high solids loading (spherical particle morphology) compared with nickel samples, which display up to 88% theoretical density due to lower solids loading (irregular particle morphology). Micro‐hardness testing and microstructure evaluation are conducted on sintered samples to investigate material properties and sintering behavior. This new carrageenan‐based route is not only simple and non‐toxic but also robust and highly versatile, showing potential to expand application of metal and metal hybrid 3D printing. Abstract : 316L stainless steel and nickel powder‐based inks are developed utilizing a carrageenan rheological modifier. Using these inks, 3D printing is achieved via material extrusion, drying, and pressureless sintering in an inert atmosphere to produce structures with 88–94% theoretical densities. This provides a simple and highly versatile 3D printing route, applicable to various metals and other powder‐based materials.